PENERAPAN PENDIDIKAN MATEMATIKA REALISTIK DALAM MENINGKATKAN HASIL BELAJAR SISWA - Alfina Lailani Rahmahdhani (Jurnal Riset Pembelajaran Matematika, 2022)
Realistic Mathematics Education Approach is one approach to teaching mathematics that is based on real or real things for students and helps students find answers to the questions given to make learning more useful. This study aims to determine the application of realistic mathematics education in improving student learning outcomes and to describe the application of realistic mathematics education that supports students' mathematics learning outcomes. This research uses data collection method with literature study or literature study method. The data sources in this study, namely 8 articles that have been accessed from relevant google schools, show that the Realistic Mathematics Education approach can improve mathematics learning outcomes in schools. This can be considered by the teacher to revive the enthusiasm of students to learn so that their learning competence will also increase, especially in today's era. Keywords: realistic mathematics education, learning outcomes